Drivers and Barriers to ESG Integration in Global Capital Markets - Ren, Jiaying (International Journal of Natural Resources and Environmental Studies, 2025)
ESG (Environmental, Social, Governance) integration has become a core framework for aligning global capital markets with sustainable development goals. According to the International Energy Agency (IEA), achieving the Paris Agreement’s net-zero target by 2050 requires annual clean energy investments to increase from 1.1 trillion in 2022 to 4 trillion by 2030[1]. As of December 2023, global climate-related funds (including mutual funds and ETFs) managed 5.4 trillion, with Europe accounting for 84% of this market[2]. However, geopolitical conflicts (e.g., the Russia-Ukraine war), economic headwinds (e.g., the 2023 global economic slowdown), and regulatory inconsistencies have hindered the deepening of ESG integration. This study aims to identify the key drivers and structural barriers of ESG integration in global capital markets using empirical data from climate fund trends, regulatory developments, and regional disparities. The main drivers include regulatory mandates (such as the EU’s Green Bond Standard 2023 and China’s ESG disclosure requirements), shifting investor preferences (especially among institutional and millennial investors, with 400 billion in net climate fund inflows in 2023), technological advancements (machine learning-based ESG data analytics by firms like MSCI and Sustainalytics[8,9]), and long-term value creation (positive correlations between ESG performance and corporate cost of capital/long-term returns). The primary barriers encompass geopolitical and economic pressures (a 23% decline in clean energy fund assets in 2023), data and methodological gaps (non-standardized ESG disclosures and conflicting ratings from agencies like CDP and Sustainalytics), short-termism (shareholder pressure for quarterly earnings over decarbonization), and market fragmentation (divergent standards between the EU’s SFDR and U.S. regulations). Regional case studies of Europe (the ESG vanguard with 875 out of 1,506 global climate funds), North America (balancing innovation and anti-ESG state laws), and the Asia-Pacific (China’s “30·60” carbon goals driving clean tech investment) further illustrate contextual dynamics[16]. To address these challenges, the study proposes solutions such as regulatory harmonization (led by the ISSB), technology-driven transparency (blockchain for green bond tracking), and investor education (mandatory ESG literacy programs). This research provides actionable insights for policymakers, investors, and companies to advance ESG integration and support the global net-zero transition.